FRAMING AND AFFIRMING THE DOMINANCE NARRATIVE: ON CULTURAL HEGEMONY AND MAINSTREAM PRINT MEDIA TREATMENT OF TWO MOMENTOUS SUPREME COURT INDIGENOUS ENTITLEMENT DECISIONS* (Canadian Journal of Native Studies, 2026)
AbstractThrough a systematic content analysis of mainstream print media treatmentof two Supreme Court rulings on Indigenous treaty entitlements,this research examines attributes of the coverage afforded to Indigenousand non-Indigenous voices. Our findings demonstrate that, with respectto narrative power, non-Indigenous interests and perspectives were predominantlyrepresented by mainstream print media. Non-Indigenousvoices were given priority and garnered more lines of direct quotation.Further, the qualitative analysis demonstrates that the mainstream printmedia coverage emphasised concerns about Indigenous Peoples’ abilitiesto manage resources competently and responsibly, while centeringon the potential implications of Indigenous sovereignty over their territoryand resources for dominant class non-Indigenous economic interests.Lastly, this research argues, through the conceptual/theoreticallens of “cultural hegemony” and “cognitive imperialism,” that mainstreamprint media function to legitimate the dominance of settler ideologyand economic interests, through the conscious representation ofIndigenous treaty rights as antithetical to Eurocentric interests and thepredominant social order. We argue that the data show a systemic bias,which functions as a key mechanism for the domination, control andsuppression of Indigenous Peoples.